Badenizacja niżowych ugrupowań kultury pucharów lejkowatych w międzyrzeczu Odry i Wisły: 3600/3500-2400/2350 przed Chr. Podstawy systematyki chronologiczno-przestrzennej - Przybył, Agnieszka (Folia Praehistorica Posnaniensia, 2018)
The main objective of the dissertation was to discuss, departing from the taxonomical viewpoint, the impact of Baden culture upon the lowlands FBC communities in the Oder and Vistula basins in the period of 3600/3500–2400/2350 BC. The work was conducted within the project „The Great Valley Area of Funnel Beaker Culture Badenization. Carpathian Eneolithic Protocivilization Centre’s Contribution to the Development of the Elbe-Saale and Vistula drainages societies on the threshold of the Early Metal Age”, financed by the Polish Committee for Scientific Research. This project included study of temporal resolution of the youngest FBC societies in the Great Valley area influenced by the protocivilization of Baden societies. Moreover, the identification of representative groups belonging to both cultures has been possible thanks to constructing a register of identifiers of the process in question, including adaptation and transformation of „initial” Baden Culture’s patterns among Kuyavian FBC societies. The project further focused upon synchronization of the lowlands phenomena with the old-highland Badenization processes in the areas of Lesser Poland, Silesia and Moravia. Systematic application of radiocarbon dating made the project particularly remarkable achievement. Altogether, 33 samples have been dated. Thanks to this method, it was possible to define a chronological position of taxons connected with the phenomena related to the Badenization process of the lowlands in three research areas: Kuyavia (mainly), Northern Greater Poland and Lower Silesia (auxiliary data). The project results contributed to the debate on the role of the Baden patterns in the latitudinal system of cultural ties in the Great Valley area between the Elbe-Saale and Vistula rivers. As these phenomena have not yet been satisfactorily recognized, especially in Greater Poland and in the Elbe river basin, a complex comparative analysis, making possible a systematic conceptualization of the process, has not been feasible. The project made possible to capture a historical context of the process of Badenization in the Great Valley zone and identified further research directions. These comprise multidimensional studies of the late and final phase in the development of Funnel Beaker Culture and the emergence of the early Bronze Age civilization in the Great Valley areas.